Bamboo reinforced prefabricated wall panels for low cost housing. (January 2017) - Puri, Vishal; Chakrabortty, Pradipta; Anand, Sourav; Majumdar, Swapan
Abstract: With the increasing population there is a tremendous exploitation of natural resources to produce conventional building materials such as bricks, cement and reinforcing bars. This exponentially increases their prices and also deteriorates the environment by production of large amount of greenhouse gases. So, there is a need to develop cheap and sustainable infrastructure. This paper presents an alternative sustainable infrastructure component – prefabricated bamboo reinforced walls beneficial for low cost housing. To determine the potential of these panels in the construction industry, the strength analysis along with the cost estimation and environmental impact analysis were also carried out for these panels. It was observed that these walls are 56% lighter in weight, 40% cheaper and have good strength as compared to partition brick walls. The benefits of these walls over the traditional brick walls were observed to be significant, through which it can be concluded that these wall panels have a great potential for low cost housing. Highlights: A new technique for development of bamboo reinforced prefabricated wall panels is described. Proposed walling system is cost effective and lighter in weight as compared to traditional brick walls. This walling system is eco-friendly, energy efficient and is helpful to develop sustainable infrastructure. Proposed wall system doesn't require sophisticated technical skills, only jointing at site is required.